Linkages between Sectors and Regions in the Aceh Economy - Miftakhul Jannah; Eddy Junaidi (Jurnal Ekonomi Pembangunan, 2022)
This study analyzes the economy of Aceh not only based on the linkage between industries but also based on the linkage between regions. The analysis used forward linkages and backward links to determine the leading sectors in Aceh. The data used is secondary data from Indonesia's 2016 Inter-Regional Input Output (IRIO) based on domestic transactions at producer prices. The data is sourced from Statistics Indonesia. The study results show that the key sectors in Aceh are Electricity and Gas and Manufacturing. These sectors have the highest spreading power (backward linkage) and sensitivity (forward linkage) because they are in the first quadrant. In addition, inter-regional linkage analysis shows that the final demand shock in Aceh has a large output impact on DKI Jakarta, North Sumatera, and Riau. On the other hand, the economy of Aceh was affected by the final demand shock from several provinces on the island of Sumatra, namely North Sumatera, Bengkulu, West Sumatera, Jambi, and Sumatra Selatan. The policy implications that can be applied to increase labor skills and management in leading sectors will have a multiplier effect on other sectors and the cooperation between provinces in a special economic zone.